TINJAUAN KRIMINOLOGIS HOMOSEKSUAL DI KABUPATEN INDRAMAYU - Kholik, Saeful (Universitas Wiralodra, 2017)
In general, there are several factors that led to the occurrence of a crime. The first is the factor that comes to or contained within the offender that predispose a person to commit a crime that arises from within itself the perpetrator based on the heredity and psychological (mental illness). The second factor is the factor that originate or are outside the personal self perpetrator. Such as a person who committed a crime because of the influence of the outside of the perpetrator based on the household and environmental factors. In the legal order of the Republic of Indonesia does not exist that specifically regarding the crime of homosexuals so often the deviation homosexuals do so more and more of the homosexuals themselves.